Advances in global leadership. Vol. 9 - Osland, Joyce; Li, Ming, active 2016; Mendenhall, Mark E., 1956- (Advances in global leadership,, 2016)
Volume 9 of "Advances in Global Leadership," includes timely and impactful articles on processes associated with effective global leadership. In these times of accelerating complexity and global inter-connectedness, a deeper understanding of the multiple contextual, organizational, and individual variables and processes associated with effective global leadership is critical. This volume contributes to bridging and integrating conceptual and practitioner perspectives in pursuing this deeper understanding. A new section of this year's volume is devoted to articles that apply and expand concepts from traditional leadership to global leadership -- an area that has heretofore received very little attention. Another new section contains articles written by consultants who provide perspectives gained from the <U+009c>front lines of global leadership development in client organizations. The volume's contributors range from well-known voices in the field to newly minted scholars with a fresh perspective.